Community Participation in Poverty Alleviation Efforts Based on Women's Empowerment through the P3EL Program in Sidoarjo Regency - Effy Wardati Maryam; Ririn Dewanti Dian Samudera Indriani (Universitas Muhammadiyah Sidoarjo, 2015)
Women are the group most severely affected by poverty, especially in case of food insecurity. As a result of these conditions, pregnant mothers could malnutrition that can potentially give birth in poor mental or health condition. Poverty reduction is not merely the issue of capital and technical skills, but also how to evoke the feeling of being able to overcome problems of their lives in a dignified manner. Empowerment of poor women do in order to find the effort that poor women can actively participate in any activities for poverty alleviation. This study aims to assess community participation, particularly of women to poverty alleviation efforts based on empowerment. This research was descriptive-exploratory using primary data sources from interviews and secondary data sources of written documents on the implementation of the Programme P3EL in Sidoarjo. Subjects were members P3EL program in 2012 and the BPMPKB (particularly the PUE) as the implementing program. The results showed that the model of participation of members to poverty alleviation efforts based on the empowerment of women through P3EL program were in the form of energy, thoughts, and cooperation. While the participation factors underlying were egoism motivation and collectivism.